2021
DOI: 10.1515/psr-2019-0128
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanics approaches for rational drug design: forcefields and solvation models

Abstract: The use of molecular mechanics (MM) in understanding the energy and target of a drug, its structures, and properties has increased recently. This is achieved by the formulation of a simple MM energy equation, which represents the sum of the different energy interactions, often referred to as “forcefields” (FFs). The concept of FFs is now widely used as one of the fundamental tools for the in silico prediction of drug-target interactions. To generate more accurate predictions in the in silico drug discovery pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…MMGBSA represents the summation of the different energy interactions otherwise called force fields (FFs) and this concept is widely used to predict in silico drug-target interactions. [51,52] Our Molecular Mechanics with Generalized Born Surface Area (MMGBSA) calculations revealed that the dominant factor responsible for the spontaneous and robust total binding energy of the complexes is the Van der Waals interaction (VDW). Based on the overall binding free energy values, it has become evident that Meliantrol and Tamarixetin represent the most effective inhibitors of HOS when compared to standard Inabenfide.…”
Section: Discussionmentioning
confidence: 99%
“…MMGBSA represents the summation of the different energy interactions otherwise called force fields (FFs) and this concept is widely used to predict in silico drug-target interactions. [51,52] Our Molecular Mechanics with Generalized Born Surface Area (MMGBSA) calculations revealed that the dominant factor responsible for the spontaneous and robust total binding energy of the complexes is the Van der Waals interaction (VDW). Based on the overall binding free energy values, it has become evident that Meliantrol and Tamarixetin represent the most effective inhibitors of HOS when compared to standard Inabenfide.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, MM approach plays an important role in understanding the ligand-protein structures, interactions and optimizing leads. It is achieved by MM potential energy function, which represents the sum of different energy terms, referred as “force fields” [ 59 ]. MM potential energy functions are used in various sampling methods, such as MD and MC (Monte Carlo).…”
Section: Computational Biology In Drug Designmentioning
confidence: 99%